Control Structure Impact on the Flying Performance of the Multi-Rotor VTOL Platform - Design, Analysis and Experimental Validation. (22nd January 2013) - Czyba, Roman; Szafranski, Grzegorz
The aim of this research is to examine the different control strategies for the unmanned aerial vehicles (UAV). The control task is formulated as an angular stabilization of the four rotor platform, and also as a tracking problem of chosen state variables. The PID algorithm has been considered in three structures in respect of the optimal control signal applied to the actuators. For better performance of the quadrotor in hover mode the cascade control system has been proposed. The simulation results of attitude control with different PID controller architectures are presented, and confirm the effectiveness of the proposed control structure and theoretical expectations. Moreover, the design and the practical realization of the control architecture on the experimental aerial vehicle are described. The fast prototyping method together with Matlab/Simulink software and DAQ hardware are used for both evolution and validation of control algorithms. The capacity of the attitude stabilization system is important in the development process of more advanced functionality of autonomous flying vehicles; therefore it needs to be highlighted and taken into careful consideration.